Eficacia del tratamiento fisioterapéutico en lesiones musculares a través de la técnica de liberación miofascial en pacientes que acuden al hospital militar de la brigada blindada hb°11 galápagos en el período de diciembre del 2009 a mayo del 2010”. - Balla Cajamarca, María Patricia (2010)
Presently investigative work is analyzed a study of the technique of liberation miofascial applied in muscular lesions whose purpose is to end up determining the applications of the combination of the physical and technical agents of the massage to offer bigger recovery and well-being to the patients. To arrive to the realization of the objectives and the confirmation of the hypothesis, it is thanks to the bias and the patients' collaboration and the professionals' of the area of Physical Therapy of the Hospital of the Armored Brigade help H-B11 Tortoises during the period of December from the 2009 to May of the 2010 you ends up obtaining a population of 26 patients, the data were obtained through the application of the investigation instruments like the observation and observation guide that were applied the patients that attended the physiotherapy area.